2010
DOI: 10.3846/bjrbe.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Crushed Waste Concrete in Stone Mastic Asphalt Mixtures

Abstract: Th e magnitude 7.6 Chi-Chi Taiwan in 1999 and the magnitude 7.9 Sichuan China in 2008 earthquakes caused many building damage and collapse, and a large amount of waste concrete caused many environmental problems. Th is study evaluates crushed waste concrete used as aggregate for stone mastic asphalt. On the basis of this study, the ANOVA of the permanent deformation test shows that the type of aggregate has a signifi cant eff ect at test temperature of 60 °C, but not signifi cantly aff ect at 25 °C. Th us, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…During the last years, research within the civil engineering sector has focused on the use of the C&D waste as new construction materials for bases, sub-bases and firms. Among these studies, Poon and Chan (2006), Aatheesan et al (2008), Courard et al (2010), and Kuo et al (2010) can be highlighted. In addition, other specific works using C&D waste in railway projects include research works by Helsen et al (1998), Indraratna and Salim (2003) and Krezel et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, research within the civil engineering sector has focused on the use of the C&D waste as new construction materials for bases, sub-bases and firms. Among these studies, Poon and Chan (2006), Aatheesan et al (2008), Courard et al (2010), and Kuo et al (2010) can be highlighted. In addition, other specific works using C&D waste in railway projects include research works by Helsen et al (1998), Indraratna and Salim (2003) and Krezel et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in order to contribute to sustainable development, several studies have been conducted dealing with the use of recycled concrete aggregates (RCA) from CDW as aggregate in hot-mix asphalt (HMA) (Cho et al, 2011;Kuo et al, 2010;Lee et al, 2012;Chen and Wong, 2013;Motter et al, 2015;Mills-Beale and You, 2010;Paranavithana and Mohajerani, 2006;Pasandín and Pérez, 2013, 2014Pérez et al, 2007 and2010;Pérez et al, 2012a;Pérez et al, 2012b;Shen and Du, 2004;Shen and Du, 2005;Tam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, several studies have indicated that HMA mixes made with RCA have higher moisture damage resistance than those made with natural aggregates (Mills-Beale and You, 2010;Paranavithana and Mohajerani, 2006;Pérez, 2013 and2014;Pérez et al, 2007 and2010;Pérez et al, 2012a;Pérez et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, research within the civil engineering sector has focused on the use of the C&D waste as the matrix of new construction materials. Among these studies Poon and Chan (2006), Courard et al (2010), Kuo et al (2010) and Čygas et al (2011) can be highlighted. Other specific studies on new materials used in railway works are: Indraratna and Salim (2003), Helsen and Van den Bulck (2005).…”
Section: Introductionmentioning
confidence: 99%